Fiscal sustainability in Saudi Arabia under Vision 2030: evidence from an ARDL analysis, 1991–2023 - Alshaikh, Said; Mansour, Hoda; Hassan, Soliman (Frontiers in Sustainability, 2026)
This study provides a rigorous assessment of Saudi Arabia’s fiscal sustainability over 1991–2023 using an advanced ARDL framework that simultaneously captures short-run fiscal dynamics and long-run equilibrium behavior. Modeling the fiscal balance as a function of government revenue, expenditure, and public debt (as shares of GDP), and supported by mixed orders of integration in the data, the ARDL bounds test confirms a stable long-run cointegrating relationship among the fiscal variables. The error-correction term is highly significant and large in magnitude, indicating rapid reversion of fiscal imbalances toward equilibrium. Structural break tests identify a major regime shift around 2016, reflecting the combined effects of the oil price collapse and the institutional reforms introduced under Vision 2030. Long-run estimates reveal that government revenue is the principal determinant of fiscal sustainability, whereas expenditure and public debt exhibit weaker long-run effects. Short-run dynamics show that the fiscal balance responds sharply and asymmetrically to changes in revenue and spending, underscoring its sensitivity to policy adjustments and external shocks. Extensive robustness checks—stability diagnostics, causality tests, and residual analysis—validate the coherence of the estimated model. Overall, the findings contribute to the fiscal sustainability literature by offering country-specific evidence that incorporates structural breaks and institutional reforms into an ARDL framework, demonstrating that Saudi Arabia’s post-2016 policy transformation has materially strengthened the economy’s long-run fiscal adjustment mechanism.